2003
DOI: 10.1046/j.1365-2419.2003.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of seasonal environmental changes on ontogenetic migrations of the squid Loligo gahi on the Falkland shelf

Abstract: The Patagonian longfin squid Loligo gahi undertakes horizontal ontogenetic migrations on the Falkland shelf: juveniles move from spawning grounds located in shallow, inshore waters (20–50 m depths) to feeding grounds near the shelf edge (200–350 m depths). Immature squid feed and grow in these offshore feeding grounds and, upon maturation, migrate back to inshore waters to spawn. The possible influence of environmental factors on L. gahi migrations was investigated using data from oceanographic transects, cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 12 publications
0
44
1
Order By: Relevance
“…Inshore spawning and nursery grounds are located in shelf waters at depths of 10-50 m. Upon growth, small immature D. gahi (5-7 cm mantle length, ML) migrate offshore to their feeding grounds located on the outer shelf at depths 130-250 m. Offshore feeding grounds are occupied by the Transient Zone that is a mixture between shelf and Sub-Antarctic waters of the Falkland Current (Arkhipkin et al, 2004). Feeding period lasts several months.…”
Section: Gahi (Formerly Loligo Gahi)mentioning
confidence: 99%
“…Inshore spawning and nursery grounds are located in shelf waters at depths of 10-50 m. Upon growth, small immature D. gahi (5-7 cm mantle length, ML) migrate offshore to their feeding grounds located on the outer shelf at depths 130-250 m. Offshore feeding grounds are occupied by the Transient Zone that is a mixture between shelf and Sub-Antarctic waters of the Falkland Current (Arkhipkin et al, 2004). Feeding period lasts several months.…”
Section: Gahi (Formerly Loligo Gahi)mentioning
confidence: 99%
“…The authors suggest that recruitment (therefore smaller squid) appears to be associated with low temperature in L. forbesi from the English Channel. Arkhipkin et al (2004) however, suggests that, in summer, immature L. gahi prefer warmer waters. Nevertheless, Loligo forbesi is the most cold water Loligo species and it has been reported that juveniles and post-larval stages are highly sensitive to temperature (Challier et al 2005).…”
Section: Gamm Results On Squid Sizementioning
confidence: 98%
“…Some maps also reveal two distinct abundance peaks, either in different coasts or one further south than the other. This could suggest that two cohorts or microcohorts exist (see Collins et al 1997Collins et al , 1999Pierce et al 2005), with different migratory behaviour -as Arkhipkin et al (2004) discussed for the migratory squid L. gahi. However, these two abundance peaks are not visible in all years.…”
Section: West Coast To North Sea Migrationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Common hake Merlucious hubbsi alone consume 8 3 10 9 kg of amphipods and euphausiids in this region (Prenski and Angelescu 1993). The continental Patagonian longfin squid stock has been estimated at 3 3 10 7 kg (Arkhipkin et al 2004 ; Table 3); seabirds consume nearly half of this stock (1.4 3 10 7 kg), potentially reducing squid densities around colonies. No biomass estimates are currently available for silversides, but regarding their restricted distribution to coastal waters (first 5 km from the coast), their abundance should be lower than the other prey considered, making this prey a candidate for potential competition and localized depletion.…”
Section: Discussionmentioning
confidence: 99%